Downwelling and Upwelling Radiance Distributions Sampled Under Cloudless Conditions in Antarctica - Ferrer-Meli, J; Cordero-Carrasco, R; Damiani, A; Jorquera, J; Rayas, J (OSA - The Optical Society, 2013)
We have sampled both the downwelling and upwelling radiance distributions at a camp located in the southern Ellsworth Mountains on the broad expanse of Union Glacier (700 m altitude, 79° 46? S, 82° 52? W). The measurements (at 320-440 nm wavelength range) were carried out under cloudless conditions by using a sky scanner system, during a campaign (in December, 2012) meant to assess the effects of the high albedo on the radiance distribution. The angular variations observed in both the downwelling and upwelling radiance distributions increase with the wavelength. However, these variations were considerably greater in the case of the downwelling radiance than in the case of the upwelling radiance. Indeed, we found that downwelling radiance tends to be less isotropic than the corresponding upwelling radiance. Regardless of the solar zenith angle and the wavelength, the minima of the downwelling and the upwelling radiance distributions were measured close to the zenith and to the nadir, respectively. The downwelling (upwelling) radiance increased nearly monotonically toward the horizon and peaked at zenith (nadir) angles that ranged from 75° to 90°. Comparisons with the UVSPEC radiative transfer model were used to weight up the response of the downwelling radiance distribution to changes in the albedo. © 2013 Optical Society of America.